2007
DOI: 10.1177/0091270006299089
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Enfuvirtide in HIV‐1‐Infected Pediatric Patients Over 48 Weeks of Treatment

Abstract: The objective of this study was to characterize the population pharmacokinetics of enfuvirtide in HIV-1-infected children and adolescents. HIV-infected patients received combination antiretroviral therapy, including enfuvirtide 2.0 mg/kg subcutaneously, twice daily. Serial and trough blood samples were collected up to 48 weeks. NONMEM was used for population pharmacokinetic analysis. Enfuvirtide exposure was calculated from individual parameter estimates derived from the final model. A total of 218 samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Patient weight was found to have an effect on CL and V, but the effect was not statistically significant. However, their predicted “adult” PK parameters were not comparable with those observed in adults by Zhang et al [113]. Additionally, in the plot of CL (L/h) vs. weight, even though the data covers a large weight range, it does not seem to capture all differences between children and adults.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Patient weight was found to have an effect on CL and V, but the effect was not statistically significant. However, their predicted “adult” PK parameters were not comparable with those observed in adults by Zhang et al [113]. Additionally, in the plot of CL (L/h) vs. weight, even though the data covers a large weight range, it does not seem to capture all differences between children and adults.…”
Section: Resultsmentioning
confidence: 76%
“…The pediatric study showed that the body weight adjusted dosing in children was independent of age, body weight, body surface area, and sexual maturity. In a population pharmacokinetic analysis study by Zhang et al ., 43 patients (20 adolescents and 23 children) were included, with a mean age of 11 years, and a mean body weight of 35.7 kg [113]. Body weight was a covariate for CL/F but not V/F.…”
Section: Resultsmentioning
confidence: 99%
“…The values for observed clearance of monoclonal and polyclonal antibodies and non-antibody proteins were obtained from the literature [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and the predicted clearance values were compared with the observed values for each drug. In this study, there were 13 monoclonal antibodies, seven polyclonal antibodies, and nine therapeutic proteins (non-antibodies).…”
Section: Methodsmentioning
confidence: 99%
“…In children, T20 has been shown to provide good virological suppression after 24 weeks of twicedaily administration [36]. PK studies have shown that the dose of 2 mg/kg twice daily provides drug exposure that is independent of age, body surface area, and pubertal stage [37][38]. However, its subcutaneous administration -with frequent local-site reactions -limits its use.…”
Section: Fusion Inhibitorsmentioning
confidence: 99%